LEGAL CONCERNS OF THE EUROPEAN UNION ON COMBATING TRAFFICKING IN HUMAN BEINGS - Diaconu, Nicoleta (International Journal of Legal and Social Order, 2021)
Trafficking in human beings is a form of crime that has spread in the contemporary era. Victims of trafficking in human beings are vulnerable people, especially women, children or jobseekers, lured by promises of advantageous jobs abroad, treatment opportunities or study offers. The European Union promotes international cooperation and makes legislative and institutional efforts to combat trafficking in human beings. The EU Strategy to Combat Trafficking in Persons (2021-2025) focuses on preventing crime, bringing traffickers to justice, protecting victims and strengthening Member States' capacity to act.